2016
DOI: 10.1038/srep23016
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired, Moisture-Powered Hybrid Carbon Nanotube Yarn Muscles

Abstract: Hygromorph artificial muscles are attractive as self-powered actuators driven by moisture from the ambient environment. Previously reported hygromorph muscles have been largely limited to bending or torsional motions or as tensile actuators with low work and energy densities. Herein, we developed a hybrid yarn artificial muscle with a unique coiled and wrinkled structure, which can be actuated by either changing relative humidity or contact with water. The muscle provides a large tensile stroke (up to 78%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 28 publications
(49 reference statements)
1
70
1
Order By: Relevance
“…Water-driven muscles have also been demonstrated by infiltration with water-absorbing polymers, such as poly(diallyldimethylammonium chloride) (PDDA). Such coiled PDDA/CNT hybrid muscles have delivered more than 40% stroke and a contractile work of 2.17 kJ/kg when exposed to between 10% and 99% relative humidity (32). Even without additional guest materials, the large surface area provided by a CNT scaffold can be used to drive actuation.…”
Section: Emerging Types Of Twisted Musclesmentioning
confidence: 99%
“…Water-driven muscles have also been demonstrated by infiltration with water-absorbing polymers, such as poly(diallyldimethylammonium chloride) (PDDA). Such coiled PDDA/CNT hybrid muscles have delivered more than 40% stroke and a contractile work of 2.17 kJ/kg when exposed to between 10% and 99% relative humidity (32). Even without additional guest materials, the large surface area provided by a CNT scaffold can be used to drive actuation.…”
Section: Emerging Types Of Twisted Musclesmentioning
confidence: 99%
“…The addition of water‐absorbing guest materials to twisted hydrophobic CNT yarns is also a commonly used mode of actuation. Kim et al prepared a crimped and creped structure using a highly twisted CNT sheet stack and a hydrophilic poly(diallyldimethylammonium chloride) (PDDA) guest . PDDA/CNT can be actuated by changes in water absorption or ambient RH.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…Carbon nanotubes (CNT) are well-known for their outstanding mechanical and electrical properties, and it has been demonstrated that twist-spun multiwalled carbon nanotubes (MWCNTs) with filled hosts can provide rapid contraction and rotary motion under different stimuli which exceed the performance of conventional artificial muscles [102,103].…”
Section: Actuators Inspired From Towel Gourd Tendrilsmentioning
confidence: 99%